2020
DOI: 10.1159/000506423
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Significance of Epigenetic Regulation of Thyroid Hormone Target Gene Expression

Abstract: Background: In previous publications, we have reported our findings demonstrating that exposure to high maternal levels of thyroid hormones (TH) has life-long effects on the wildtype (WT, without THRB mutation) progeny of mothers with resistance to thyroid hormone beta (RTHβ). The mechanism of this epigenetic effect remains unclear. Objectives: We reviewed the mechanisms involved in the epigenetic regulation of TH target genes and understand how they may explain the reduced sensitivity to TH in the WT progeny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The reduced TSH levels at age 50 in women exposed to famine conditions in mid gestation might be the result of epigenetic alterations within the regulation of the HPT axis. It has been suggested that tissue-specific changes in the epigenetic expression of deiodinase enzymes, which activate and deactivate thyroid hormones, may be a putative mechanism by which such changes in the regulation of the HPT axis can occur (1,36,37). Research by Anselmo et al (2019) on the intergenerational effect of foetal exposure to abnormally high maternal thyroid hormone levels in an Azorean population has shown that even in the third generation, reduced sensitivity to administered thyroid hormones is found (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced TSH levels at age 50 in women exposed to famine conditions in mid gestation might be the result of epigenetic alterations within the regulation of the HPT axis. It has been suggested that tissue-specific changes in the epigenetic expression of deiodinase enzymes, which activate and deactivate thyroid hormones, may be a putative mechanism by which such changes in the regulation of the HPT axis can occur (1,36,37). Research by Anselmo et al (2019) on the intergenerational effect of foetal exposure to abnormally high maternal thyroid hormone levels in an Azorean population has shown that even in the third generation, reduced sensitivity to administered thyroid hormones is found (37).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Anselmo et al (2019) on the intergenerational effect of foetal exposure to abnormally high maternal thyroid hormone levels in an Azorean population has shown that even in the third generation, reduced sensitivity to administered thyroid hormones is found (37). They speculated that the pituitary expression of the deiodinase 3 enzyme, which inactivates thyroid hormones by deiodination of the inner ring of both T4 and T3, is increased after exposure to maternal hyperthyroidism during pregnancy (36). The opposite might be true in the context of maternal malnutrition during pregnancy, which has been shown to lead to decreased thyroid hormone levels, specifically T3, compared to well-nourished women (38).…”
Section: Discussionmentioning
confidence: 99%
“…It may also lead to a deficient supply of L-T 4 and a deficit in the mechanism of action of this hormone at the brain level and, consequently, a state of mild THH in the CNS of the patient with CH. To our knowledge, this hypothesis has not been explored at a molecular level in patients or animal models; however, previous research has shown a link between neonatal thyroid status and the sensitivity to THs at the brain level [ 123 , 124 , 125 , 126 , 127 , 128 ]. Srichomkwun et al [ 125 ] demonstrated that the exposure to high concentrations of THs during intrauterine life causes brain THH in humans and mice.…”
Section: Factors Contributing To the Establishment Of Neuropsychologi...mentioning
confidence: 99%
“…This effect is persistent until adulthood in both species and is accompanied by changes in the expression of deiodinases in the hypothalamus and pituitary. Interestingly, THH derived from intrauterine hyperthyroidism is persistent throughout three generations in the male human line [ 124 ] and is linked to an epigenetic phenomenon in the genes encoding the various molecules involved in the supply or mechanism of action of THs in the CNS [ 123 ].…”
Section: Factors Contributing To the Establishment Of Neuropsychologi...mentioning
confidence: 99%
“…The transcriptional mechanisms controlling thyroid development and function, including epigenetic aspects, have been deeply investigated [16]. Although the regulation of mRNA stability is also an important mechanism regulating differential gene expression, particularly in developmental processes [17], its role in congenital hypothyroidism has been neglected.…”
Section: Introductionmentioning
confidence: 99%